1966
DOI: 10.1002/pol.1966.150040210
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl polymerization by cobaltic ions in aqueous solution: Part I. Polymerization of methyl methacrylate

Abstract: synopsisPolymerization of methyl methacrylate initiated by cobaltic ions in perchloric, nitric and sulfuric acids was studied in the temperature range 15-25°C. In all three acids, water oxidation occurred as a side reaction. In HC10, and HNOa media monomer oxidation was shown to be an additional complicating, feature. Rates of cobaltic ion disappearance, monomer disappearance, and chain lmgths of polymers were measured with variations in [MI, [Co3+], [H+], initially added [Co*+], and temperature. In HClOl and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Both systems demonstrate the presence of the Co(II)—Co(III) species which is consistent with the predictions of the Haber–Weiss scheme. The mechanism presented by Jijie et al5, 6 offers a better explanation of the observed behavior: …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Both systems demonstrate the presence of the Co(II)—Co(III) species which is consistent with the predictions of the Haber–Weiss scheme. The mechanism presented by Jijie et al5, 6 offers a better explanation of the observed behavior: …”
Section: Resultsmentioning
confidence: 97%
“…In addition to the reactions shown above, termination will occur by the usual transfer and disproportionation reactions. The concentration of the metal‐catalysts is a crucial parameter for the radical polymerization processes to occur 5–7. Cobalt complexes are usually used in conjunction with peroxides and tertiary amines.…”
Section: Introductionmentioning
confidence: 99%
“…Both systems demonstrate the presence of the Co(II)-Co(III) species which is consistent with the predictions of the Haber-Weiss scheme. The mechanism presented by Jijie et al 5,6 offers a better explanation of the observed behavior:…”
Section: Differential Scanning Calorimetry Measurementsmentioning
confidence: 92%
“…The concentration of the metalcatalysts is a crucial parameter for the radical polymerization processes to occur. [5][6][7] Cobalt complexes are usually used in conjunction with peroxides and tertiary amines. However, tertiary amines can also act as promoters for the dissociation of organic peroxides and aid the initiation of low temperature polymerization processes.…”
Section: Introductionmentioning
confidence: 99%
“…Duplicate runs were mer, MMA (Sisco-Chem.) was purified by the carried out for the determination of the rate of standard procedure, 16 distilled repeatedly in nimonomer disappearance as well as the rate of cetrogen atmosphere, and stored in dark brown botric ion disappearance. tles at 5ЊC.…”
Section: Methodsmentioning
confidence: 99%